Explaining cross-country differences in contact rates - Annelies G. Blom (University of Essex, Institute for Social and Economic Research (ISER), 2009)
In the European Social Survey (ESS) contact rates differ across countries. These differences are broadly due to (1) differences in survey implementation, (2) differences in population characteristics associated with contact propensity and (3) differences in the association between 1 or 2 and contact propensity. This paper investigates correlates of contact within and across ESS countries by decomposing cross-country differences in predicted mean contact propensities into (population and fieldwork) characteristics effects, coefficients effects and a pseudo-interaction effect. The findings shed light on the cross-national comparability of the manipulable aspects of the contacting process. In addition, we distinguish factors explaining withincountry contact propensity from factors explaining cross-country differences.
Keywords: 330